2022
DOI: 10.18280/ijht.400227
|View full text |Cite
|
Sign up to set email alerts
|

Tilt Angle Optimization and Investigation of the Behavior of a Flat Plate Solar Collector Using MATLAB for Kurdistan Climate Conditions-Iraq

Abstract: The goal of this study is to investigate the heat transfer as well as optimizing the tilt angle of an active flat plate solar collector. In addition, MATLAB software is used for study the flat plate solar performance of the collector. The entire test rig, with a complete control system, has been set up to collect practical data in September and October 2021. The results showed that the collector efficiency rises with the usable heat rate, peaking at 77% in the autumn (14 October) at the optimal heat rate of 97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Double glass-acrylic-covered SAHs showed comparable daily thermal performance and enhanced durability. Rashid et al 11 studied enhancing tilt angle and heat transfer efficiency of an active flat plate solar collector using MATLAB software. Data showed a peak efficiency of 77% with an optimal heat rate of 975 W and 64°C output water temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Double glass-acrylic-covered SAHs showed comparable daily thermal performance and enhanced durability. Rashid et al 11 studied enhancing tilt angle and heat transfer efficiency of an active flat plate solar collector using MATLAB software. Data showed a peak efficiency of 77% with an optimal heat rate of 975 W and 64°C output water temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, solar energy deployed to conserve 1383 kW of power annually. In addition, it is environmental friend; by reducing the annual Emissions of CO2 around 781 kg for every flat plate solar collecoter [3].…”
Section: Introductionmentioning
confidence: 99%
“…showed that dust and dirt could significantly contribute to reducing the solar reflectivity of the RCM. Singh and Rawat [21] highlight the thermal performance of cool roofs with various surface coatings in different climate zones for buildings, along with additional advantages, limitations, and recommendations for further study. The average energy-saving impact of the roof varies by climate zone and ranges from 15% to 35.7%, according to the literature review findings (Composite, Temperate, Tropical, Hot, and Warm-Humid).…”
Section: Introductionmentioning
confidence: 99%